High dose of vesicular stomatitis virus-vectored Ebola virus vaccine causes vesicular disease in swine without horizontal transmission. Issue 1 (1st January 2021) - Morozov, Igor; Monath, Thomas P.; Meekins, David A.; Trujillo, Jessie D.; Sunwoo, Sun-Young; Urbaniak, Kinga; Kim, In Joong; Narayanan, Sanjeev K.; Indran, Sabarish V.; Ma, Wenjun; Wilson, William C.; O'Connor, Cassandra; et al.
ABSTRACT : The recent impact of Ebola virus disease (EVD) on public health in Africa clearly demonstrates the need for a safe and efficacious vaccine to control outbreaks and mitigate its threat to global health. ERVEBO® is an effective recombinant Vesicular Stomatitis Virus (VSV)-vectored Ebola virus vaccine (VSV-EBOV) that was approved by the FDA and EMA in late 2019 for use in prevention of EVD. Since the parental virus VSV, which was used to construct VSV-EBOV, is pathogenic for livestock and the vaccine virus may be shed at low levels by vaccinated humans, widespread deployment of the vaccine requires investigation into its infectivity and transmissibility in VSV-susceptible livestock species. We therefore performed a comprehensive clinical analysis of the VSV-EBOV vaccine virus in swine to determine its infectivity and potential for transmission. A high dose of VSV-EBOV resulted in VSV-like clinical signs in swine, with a proportion of pigs developing ulcerative vesicular lesions at the nasal injection site and feet. Uninoculated contact control pigs co-mingled with VSV-EBOV-inoculated pigs did not become infected or display any clinical signs of disease, indicating the vaccine is not readily transmissible to naïve pigs during prolonged close contact. In contrast, virulent wild-type VSV Indiana had a shorter incubation period and was transmitted to contact control pigs. These results indicate that the VSV-EBOV vaccine causes vesicular illness in swine when administered at a high dose. Moreover, the study demonstrates the VSV-EBOV vaccine is not readily transmitted to uninfected pigs, encouraging its safe use as an effective human vaccine.